Cardiovascular disease in hereditary haemophilia: The challenges of longevity. (21st February 2022) - Shapiro, Susan; Benson, Gary; Evans, Gillian; Harrison, Catherine; Mangles, Sarah; Makris, Mike
Abstract: The development of effective and safe treatments has significantly increased the life expectancy of persons with haemophilia (PWH). This has been accompanied by an increase in the comorbidities of ageing including cardiovascular disease, which poses particular challenges due to the opposing risks of bleeding from haemophilia and antithrombotic treatments versus thrombosis. Although mortality secondary to coronary artery disease in PWH is less than in the general population, the rate of atherosclerosis appears similar. The prevalence of atrial fibrillation in PWH and risk of secondary thromboembolic stroke are not well established. PWH can be safely supported through acute coronary interventions but data on the safety and efficacy of long‐term antithrombotics are scarce. Increased awareness and research on cardiovascular disease in PWH will be crucial to improve primary prevention, acute management, secondary prevention and to best support ageing PWH.